The Culturalization of the Linguistic Sign: Foundation of the Transmission of Culture through Language (London Journal of Research In Humanities and Social Sciences, 2025)
This research explores the character of the linguistic sign that predisposes the language to spread culture. Every language conveys a culture of which it is both producer and product (Porcher, 1995). Language is therefore a carrier of culture. Starting from this evidence, a logical problem arises: for language, as a system of signs, to effectively be the vehicle of culture, the signs that compose it must have a character that predisposes them to this function. However, according to one of the foundations of modern linguistics, the linguistic sign is arbitrary (Saussure, 1916). In addition, none of its other known characters is linked to its capacity to convey culture. It is therefore possible to define a new character to express this general principle. This character, relating to the tendency of the linguistic sign to make the language cultural, will be called “culturalization of the linguistic sign”. This character could be dichotomous and also applicable to non-linguistic signs. To conduct this research, we used non-probability sampling by purposive choice and collected data using two interview guides from 35 resource persons. The data, collected mainly in three languages or dialects (french, gùngbè, fɔngbè), enriched by online information and analyzed by the content analysis method according to the “box” procedure (Bardin, 1991), show that the culturalization of the linguistic sign is a general principle applicable to all languages. The study made it possible to conceptualize the “culturalization of the linguistic sign”, to describe its dimensions and bases, and to demonstrate that this characteristic predisposes the language to the transmission of culture.
Keywords: Phenomenology; ASD; late modernity; complex phenomenon; psychotherapeutic discourse; medical discourse; psychotherapeutic discourse integrated into fiction; conceptual metaphor in therapy; agent and client of psychotherapeutic discourse; language representation of feelings and emotions.; existential psychoanalysis; Phenomenological clinic; Environmental devastation; Patriarchal Categories; Ecological Problem; Vandana Shiva.; distributive law; the right to deferred exchange; capital; the triad; the riddle of Varys; terminology; term; graded series of terms; graduality; terminological gradation.; language; Culture; linguistic sign; culturalization.